2016
DOI: 10.1017/s1041610216001204
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to diagnosis and management in dementia care: views of future general practitioners

Abstract: Considerable international governmental support is focused on the timely diagnosis of dementia and post-diagnostic care of people with dementia. Identifying those at high risk of dementia is one approach to timely diagnosis. General practitioners (GPs) are well-placed clinicians in the community to provide both pre- and post-diagnostic dementia care. However, GPs have in the past consistently demonstrated low confidence in both diagnosing dementia and providing care for these complex patients particularly for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 14 publications
2
22
0
4
Order By: Relevance
“…National strategies developed to address the increased prevalence of dementia have emphasised the role of GPs in successful implementation but dementia care in the community can be challenging . In common with their hospital‐based colleagues, General practitioners find the management of the behavioural and psychological symptoms of dementia (BPSD) particularly difficult …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…National strategies developed to address the increased prevalence of dementia have emphasised the role of GPs in successful implementation but dementia care in the community can be challenging . In common with their hospital‐based colleagues, General practitioners find the management of the behavioural and psychological symptoms of dementia (BPSD) particularly difficult …”
Section: Introductionmentioning
confidence: 99%
“…8,9 In common with their hospital-based colleagues, 10 General practitioners find the management of the behavioural and psychological symptoms of dementia (BPSD) particularly difficult. [11][12][13][14] Behavioural and psychological symptoms of dementia encompass behaviours such as aggression, wandering, sexual disinhibition, agitation, and symptoms such as anxiety, depression, and delusions. Most people with dementia will experience BPSD at some time during their illness.…”
Section: Introductionmentioning
confidence: 99%
“…Further, primary care clinicians themselves are familiar with the process of risk assessment. A survey of primary care physician trainees found that they were also keen to implement a dementia risk assessment strategy to assist in earlier identification 25. However, potential barriers have been identified in previous studies, such as system-related factors (lack of support, time constraints)26 27 and training in dementia,27 which would need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…When assessing the differences in the importance of each benefit and risk among the different groups of respondents we found that GPs appeared less sensitive to the "patient's right to know", "access to medical research" and "initiation of symptomatic drug-treatment"; GPs could thereby be the main target of the previously described recommendation. However, although in some reports GPs are portrayed as barriers to diagnosis, and accused of fatalism regarding NCD, with a "deficit model of GPs behavior and attitudes" [6], a growing body of evidence indicates that the attitude of the majority of GPs is not characterized by diagnostic and therapeutic nihilism and GPs are very positive about their key role in NCD care [34,35]. For many patients, consultations with GPs where they discuss for the first time a cognitive complaint are positive experiences, with feelings of support, familiarity and confidence.…”
Section: Discussionmentioning
confidence: 99%